The attempted murder of Teddy Roosevelt : a John Hay mystery - Solomon, Burt (Solomon, Burt. John Hay mystery., 2019)
"Theodore Roosevelt had been president for less than a year when on a tour in New England his horse-drawn carriage was broadsided by an electric trolley. TR was thrown clear but his Secret Service bodyguard was killed instantly. The trolley's motorman pleaded guilty to manslaughter and the matter was quietly put to rest. But was it an accident or an assassination attempt...and would there be another "accident" soon?"--